Poverty in America : an encyclopedia - Lawson, Russell M., 1957- (Gale virtual reference library., 2008)
How has the U.S. dealt, throughout its long history, with one of the worlds oldest problems? Although poverty has always been part of the human experience, societal reactions and responses to it have been as varied as the condition has been static. Poverty in America has its own turbulent history of causes, effects, and remedies, from debtor's prison to the War on Poverty, from Social Darwinism to food stamps. This in-depth encyclopedia covers the entire history of American poverty from every angle--historical, social, cultural, political, spiritual, and literary. How has poverty been defined in America? What has been done to prevent it? How have minority groups been affected? How has the church reacted? And what, if anything, can be done to eliminate it? Poverty in America covers these issues in vivid detail, from the colonial period to the Industrial Revolution to the global economy of the 21st century. Impactful primary document excerpts from key periods throughout American history are also included, providing firsthand accounts from all sides of the issue. A chronology of events and an extensive bibliography round out this fascinating work.